A proposal for sectorial organizing and quality standards in therapeutic apheresis: The therapeutic apheresis unit (TAU) standards. Issue 4 (18th February 2019) - Pierelli, Luca; Iaconianni, Vincenzo; Vacca, Michele
Abstract: Therapeutic apheresis (TA) includes a wide range of therapeutic procedures based on the separation of blood components and the collection of cells with therapeutic activity or the removal of unwanted plasma or cellular components involved in the etiology of various hematologic, renal, neurological, and medical diseases. The complexity of these interventions requires an organizing model to assure a proper clinical environment, technology, quality requirements, and personnel as well as an active system for outcome monitoring for safety and efficacy. Finally, a structured organizing model may favor the efficiency of the TA unit and economic affordability. Here, we describe the more relevant characteristics of a model of TA standards, named TA unit (TAU) standards, that may help to establish a quality program in units working in the field of TA (shown as supplementary material and available athttp://www.ifeit.org/pdf/TAU_Standards_3.0.pdf .